2017
DOI: 10.4085/1062-6050.52.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Head-Impact–Measurement Devices: A Systematic Review

Abstract: Context: With an estimated 3.8 million sport-and recreation-related concussions occurring annually, targeted prevention and diagnostic methods are needed. Biomechanical analysis of head impacts may provide quantitative information that can inform both prevention and diagnostic strategies.Objective: To assess available head-impact devices and their clinical utility.Data Sources: We performed a systematic search of the electronic database PubMed for peer-reviewed publications, using the following phrases: accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 114 publications
2
119
0
Order By: Relevance
“…Further, 95th percentile values are more representative of the magnitudes for head impacts typically associated with injury. 32,42 Risk-weighted exposure is an aggregate measure that combines impact frequency and magnitude as a means of considering overall head impact exposure. 12,40,42,53 The risk of concussion was computed for each head impact sustained by an athlete, and then these individual risk values were summed together into one measure.…”
Section: Comparison To Other Populationsmentioning
confidence: 99%
“…Further, 95th percentile values are more representative of the magnitudes for head impacts typically associated with injury. 32,42 Risk-weighted exposure is an aggregate measure that combines impact frequency and magnitude as a means of considering overall head impact exposure. 12,40,42,53 The risk of concussion was computed for each head impact sustained by an athlete, and then these individual risk values were summed together into one measure.…”
Section: Comparison To Other Populationsmentioning
confidence: 99%
“…However, the ability to implement the use of biomechanical data that predict concussion remains elusive. 19,25 Nevertheless, high-acceleration head impacts (HHIs) have consistently been shown to elevate the risk of neurological injury. 6 In a study of 54,247 head impacts captured by helmet accelerometry in high-school athletes, there was a 6.9% incidence of mTBI when the impact exceeded 5582.6 rad/sec 2 in rotational acceleration and 96.1g in linear acceleration, while the incidence of mTBI was 0.00004% when the impact magnitude fell below these values.…”
mentioning
confidence: 99%
“…Collectively, these studies agree that peak strains and stresses of concussive injury are located near the brainstem in central brain areas such as the midbrain, thalamus, and corpus callosum regardless of the actual head impact location. However, research has also suggested that head impact sensors do not yet have the sensitivity needed to accurately locate the impact azimuth or determine a reliable g‐force threshold for concussion diagnosis (Allison, Kang, Bolte, Maltese, & Arbogast, ; Guskiewicz & Mihalik, ; King, Hume, Gissane, Brughelli, & Clark, ; Kutcher et al, ; O'Connor, Rowson, Duma, & Broglio, ). For example, a study seeking to quantify head impact exposure for a collegiate women's soccer team over the course of a season found that head impact sensor data had both a high level of false positives and false negatives when compared to video analysis of potential concussive hits and a medical assessment of concussive injury (Press & Rowson, ).…”
Section: Discussionmentioning
confidence: 99%